Dampak Pemanfaatan Media Interaktif Terhadap Peningkatan Hasil Belajar: Meta-Analisis - Renny Permata Saputri; Asmar Yulastri; Ganefri; M. Giatman; Dedy Irfan; Hansi Effendi (Postgraduate, University of Mataram, 2025)
This study evaluates the impact of interactive media on students' learning outcomes through a meta-analysis approach. A total of 25 relevant studies published between 2019 and 2024 were analyzed using the Restricted Maximum Likelihood (ML) method in a random-effects model. The results show a moderate effect size (Cohen’s d = 0.495) with substantial heterogenety (I² = 89.27%). Publication bias was tested using a funnel plot, Egger’s test, and fail-safe N analysis, confirming the validity of the findings. The results indicate that interactive media significantly enhance student learning outcomes across various educational contexts. These findings suggest that teachers and policymakers should integrate interactive media into science education to foster student engagement and improve learning effectiveness. Future research should explore the long-term impact and optimal implementation strategies for interactive media in diverse learning environments.